2008
DOI: 10.1002/jbm.a.32142
|View full text |Cite
|
Sign up to set email alerts
|

Composite implantation of mesenchymal stem cells with endothelial progenitor cells enhances tissue‐engineered bone formation

Abstract: For successful tissue engineering, neovascularization of the implanted tissue is critical. Factors generated by endothelial cells are also considered crucial for the process of osteogenesis. The direct effects of supplementing tissue engineered constructs with cultured endothelial progenitor cells (EPCs) for enhancing bone regeneration have not been reported. In this study, we investigated the potential of EPCs to facilitate neovascularization in implants and evaluated their influence on bone regeneration. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
63
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 58 publications
(95 reference statements)
3
63
0
Order By: Relevance
“…Such increase in vascularization could make a direct contribution to bone formation, as evident in the increased ectopic bone formed in the EPC/MSC constructs, suggesting an interdependent relationship between vascularization and bone formation. Usami et al found a 1.6-fold higher capillary score formation on both the surface and central regions of canine-EPC/MSC scaffolds, accompanied by a 1.3-fold increase in bone area regenerated in subcutaneous implants [14], while Seebach et al demonstrated increased early vascularization in the first 4 weeks with improved bone regeneration and healing in a rat critical-sized femoral defect model after EPC/MSC implantation compared to MSC alone [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such increase in vascularization could make a direct contribution to bone formation, as evident in the increased ectopic bone formed in the EPC/MSC constructs, suggesting an interdependent relationship between vascularization and bone formation. Usami et al found a 1.6-fold higher capillary score formation on both the surface and central regions of canine-EPC/MSC scaffolds, accompanied by a 1.3-fold increase in bone area regenerated in subcutaneous implants [14], while Seebach et al demonstrated increased early vascularization in the first 4 weeks with improved bone regeneration and healing in a rat critical-sized femoral defect model after EPC/MSC implantation compared to MSC alone [13].…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have cocultured putative EPC with MSC or osteoblast-like cell types on the premise that this strategy will generate prevascular networks within bone tissue-engineered grafts to aid bone repair [13][14][15][16][17][18]. However, the majority of studies used ECs [19][20][21][22][23] rather than ECFC.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of scaffold materials have been investigated for EC and MSC cocultures, including poly(e-caprolactone) (PCL), starch-based scaffolds with a fiber size of more than 200 mm, 16,17 hydroxyapatite (HA) and b-TCP (Ca 3 (PO4) 2 ) porous discs, 28 hydrophilic and hydrophobic titanium surfaces, 27 collagen mesh scaffolds, 29 and PCL-HA composite membranes. 30 Recently, porous microfiber mesh scaffolds made of biodegradable PCL have been developed using electrospinning.…”
Section: Introductionmentioning
confidence: 99%
“…9 Organized functional networks have been obtained in vivo by combining an endothelial cell source, for example, cord blood and peripheral blood-derived endothelial progenitor cells (EPCs) or human umbilical vein endothelial cells (HUVECs), with a mural cell source, for example, multipotent stromal cells (MSCs) or smooth muscle cells, in matrigel plugs. 6,[10][11][12] Previous studies focusing on prevascularized bone tissue engineering [13][14][15][16][17] have included several osteogenic cell sources, among which the primary osteoblasts 15,16 and the more proliferative MSCs 11,18 were most commonly used.…”
mentioning
confidence: 99%